A Multiplicative Formula for Aggregating Probability Assessments - Bordley, Robert F. (Management Science, 1982)
This paper presents an axiomatic approach to the problem of aggregating expert assessments of an event's probability into some group probability assessment. A multiplicative formula is derived.